GRK5‐mediated inflammation and fibrosis exert cardioprotective effects during the acute phase of myocardial infarction. Issue 2 (20th January 2023) - Nagasaka, Akiomi; Terawaki, Tsuyoshi; Noda, Makoto; Takashima, Miyuki; Fujino, Mika; Yamauchi, Yuto; Arawaka, Shigeki; Kato, Takeo; Nakaya, Michio
Abstract : During myocardial infarction (MI), cardiac cells at the infarcted area undergo cell death. In response, cardiac myofibroblasts, which are mainly differentiated from resident fibroblasts upon inflammation, produce extracellular matrix proteins such as collagen to fill the damaged areas of the heart to prevent cardiac rupture. In this study, we identified a cardioprotective role of G‐protein‐coupled receptor kinase 5 (GRK5) in MI. GRK5 expression was found to increase in the mouse heart after MI and was highly expressed in cardiac fibroblasts/myofibroblasts. In fibroblasts/myofibroblasts, GRK5 promoted the expression of inflammation‐related genes through nuclear factor‐κB activation, leading to an increase in the expression levels of fibrosis‐related genes. Bone marrow transfer experiments confirmed that GRK5 in fibroblasts/myofibroblasts, but not in infiltrated macrophages in the infarcted area, is mainly responsible for GRK5‐mediated inflammation in infarcted hearts. In addition, inflammation and fibrosis at the infarcted area were significantly suppressed in GRK5 knockout mice, resulting in increased mortality compared with that in wild‐type mice. These data indicate that GRK5 in cardiac fibroblasts/myofibroblasts promotes inflammation and fibrosis to ameliorate the damage after MI. Abstract : G‐protein‐coupled receptor kinase 5 (GRK5) is highly expressed in cardiac myofibroblasts and initiates inflammation through nuclear factor‐κB activation, leading to an increase in the expression levels of fibrosis‐related genes in the acute phase of myocardial infarction. Thus, GRK5 in cardiac myofibroblasts is an important molecule that promotes inflammation and fibrosis to ameliorate the damage after myocardial infarction.